The Use of Biological Feedback in Complex Treatment of Patients with Rheumatoid Arthritis and Systemic Sclerosis - Grekhov, R; Suleymanova, G; Shilova, L; Levkina, M; Rogatkina, T (KnE Life Sciences, 2018)
There are significant emotional problems in patients with systemic sclerosis (SS) and rheumatoid arthritis (RA), including most expressed symptoms of anxiety and depression that complicate the process of social and psychological adaptation of patients, reduce the level of subjective control as an attribute of personal responsibility for controlling their disease. The effectiveness of the biofeedback (BFB) training in the treatment of patients with rheumatoid arthritis and systemic sclerosis is analyzed. Analysis of the effectiveness of treatment was conducted by studying the dynamics of a number of psychological indices (the level of subjective control, reactive and personal anxiety, depression) and their comparison in patients of the main and control groups before and after the treatment. Correction of the psycho-emotional state of patients with SS and RA was carried out using biofeedback (BFB), based on the principle of self-regulation of body functions using external feedback systems. There was a significant reduction in anxiety and depressive reactions in patients, during the process of BFB therapy, accompanied by a significant decrease of scores by Spielberger–Khanin and Beck psychological tests, noted a significant effect of increasing the level of subjective control that can improve the effectiveness of therapy and long-term disease prognosis. Thus, the additional application of BFB training in complex treatment of SS and RA patients promoted the improvement of the efficiency of the treatment and rehabilitation carried out and the improvement of the patients’ quality of life. Keywords: BFB training, systemic sclerosis, rheumatoid arthritis, rheumatic diseases, reactive anxiety, personality anxiety, depression, level of subjective control